Pemanfaatan Web dalam Model Problem Based Learning - abduh, nis rokha (Madaniyah, 2018)
A study in general will be more effective when carried out through the learning model tha includes family information, this is because the information processing model emphasize show a person thinks and how it impacts informasi. ways to process this much criticism leveled at the way teachers teach that too much emphasison mastery of concepts/information ageand technological development sinfluence the way teachers in presenting one ofthe learning model of constructivism. The process of learning that is constructivist view that learningis not knowledge knowledge et transferactivities from teachers to students, but rather an activity that allows learners to build their knowledge, including how to solve the problem with various solutions. Problem-based learning modelis a model of learning that is based on them any is sues that requirean authentic investigation that requiresthe completion of the investigation in to the realof there alproblems.Â Key Words: Learning Process, Problem Based Learning, Website.